Resource sharing in the UK public library system: an update. Issue 4 (21st November 2016) - Froud, Robert
Abstract : Purpose: This paper aims to review the position of UnityUK and FABLibraries (Find a Book in Libraries) some five years after a review by the same author (with Elisabeth Robinson) was published in 2011. Design/methodology/approach: The UnityUK service and its co-service FABLibraries is placed in the current service and political context: changing politics and reductions in public service. The conclusions of a survey conducted by the University of Sheffield are noted as current technical developments. Findings: Subscriptions to UnityUK remain stable despite an overall decline in interlending. The FABLibraries service is well positioned to play a key role in the creation of a single digital presence for public libraries in England and in the UK. Practical implications: The outcome of major recent political change in respect of public service is not yet known, but there is reason to be confident about the role of the two services in supporting resource discovery and supply. Social implications: The FABLibraries service is well positioned to be the major building block in a national e-public library platform. This would provide a cost-effective means of making national resources accessible to everyone who can get online. Originality/value: The author provides an up-to-date perspective of the impact of change, recent government reports and public sector austerity on interlending and the position of key resource discovery tools in that environment.